Recurrent Pott Puffy Tumor in a Child With Frontonasal Dermoid: An Unusual Presentation. Issue 8 (13th July 2022) - Agarwal, Pallavi; Pandhi, Aashima; Litra, Florentina; Barr, Lori
Abstract : We present a case of Pott puffy tumor in a 21-month-old male, the youngest patient ever reported to have developed this complication and the first ever to have developed recurrence from an infected frontonasal dermoid. Hence, by reporting this case, we want to raise awareness about the importance of early recognition of Pott puffy tumor; and the need to meticulously evaluate and resect any craniofacial dermoid that could potentially lead to recurrence and intracranial complications if left unrecognized.